تكنولوجيا الواجهات التفاعلية والذكية وأثرها البيئي - عفيفي، نها سيد محمد; عفيفي، وائل محمد كامل السيد (الجمعية العربية للحضارة والفنون الإسلامية, 2023)
ساهم التطور العلمي والتكنولوجي على إثراء العمارة بشكل عام، حيث حققت تكنولوجيا الواجهات العديد من التطورات في كل من مواد وتكنولوجيا البناء ولاسيما مع ظهور العمارة المتقدمة تكنولوجيا، مثل العمارة المستدامة والعمارة التفاعلية والعمارة الذكية. إن الواجهات هي الأجزاء الأكثر وضوحا في المبنى وتشكل نمط المبنى من خلال عناصرها، وتحمل تكنولوجيا تفاعلية وذكية تجعل المبنى قابل للتكيف والتفاعل مع الظروف البيئية، مع تحديد الأثر البيئي له. يحدد الأثر البيئي الآثار البيئية الناتجة عن إقامة المشروعات، وتشمل الخامات وتكنولوجيا البناء والإنتاج... والتي تؤثر على النظام البيئي، وتقييم الآثار المحتملة سلبية كانت أم إيجابية لمشروع ما مقام على البيئة الطبيعية. يهدف الأثر البيئي إلى الحد من التلوث البيئي، وتحقيق التوازن ما بين البيئة والتنمية، الحفاظ على النظام البيئي. أضافت التكنولوجيا المتقدمة ولاسيما تكنولوجيا الواجهات التفاعلية والذكية في الواجهات نمطا جديدا للمباني يتصف بالبساطة المعقدة، في كل من الشكل وتكنولوجيا البناء، وعلاقتها بالنظام البيئي، من خلال عرض وتحليل نماذج توضيحية لمباني ذات واجهات تفاعلية وذكية وتحديد الأثر البيئي لها ومدى توافقها مع الأنظمة البيئة المستدامة، واختص البحث بتحليل أنواع الواجهات التفاعلية من خلال تحديد: الفكرة التفاعلية، وتكنولوجيا التفاعل، والأثر البيئي. تتنوع الواجهات التفاعلية بأنواع من التفاعل الديناميكي: (ميكانيكي، إيهامي، بواسطة المستخدم، رقمي) مما يؤثر في شكل الواجهة، وتفاعلها وأثرها البيئي. تعتمد تكنولوجيا الواجهات التفاعلية على تكنولوجيا التكسيات المطبقة، ومنها "الواجهات ذات التهوية" والتي تعتمد على وجود هيكل التثبيت، وتتميز بالتقليل من كمية مواد البناء، وخفض درجة حرارة المبنى وترشيد استهلاك الطاقة الكهربية. تشتمل الواجهات التفاعلية والذكية على مواد تكسية خارجية متطورة ذات طبيعة تفاعلية، مثل تكسيات الالكوبوند والدهانات التفاعلية والزجاج الذكي.... تتميز مواد التكسية التفاعلية بمواصفات صناعية وبيئية من أهمها مقاومة العوامل الجوية وأشعة الشمس والرطوبة والآفات والحرائق، وخفض استهلاك الطاقة الكهربية، والاستفادة من الطاقة الشمسية الطبيعية وطول عمرها الزمني وسهولة الصيانة. تتوافق الواجهات التفاعلية والذكية مع الأنظمة البيئية المستدامة عندما يتوفر فيها معايير الأثر البيئي. The scientific and technological development has contributed to the enrichment of architecture in general, as facade technology has achieved many developments in both building materials and technology, especially with technologically advanced architecture, such as sustainable architecture, interactive architecture and smart architecture. The facades are the most visible parts of the building and shape the building style through its elements, with an interactive and smart technology that makes the building adaptable and interacting with environmental conditions, while determining its environmental impact. The environmental impact determines the environmental impacts resulting from the establishment of projects, including raw materials, construction technology, and production... which affect the ecosystem, and assesses the potential negative or positive effects of a project on the natural environment. The environmental impact aims at reducing environmental pollution, achieving a balance between environment and development, and preserving the ecosystem. The advanced technology, especially the interactive and smart facades technology, added a new style of buildings that is characterized by complex simplicity, in both form and construction technology, and its relationship to the ecosystem, by presenting and analyzing illustrative models of buildings with interactive and smart facades, determining their environmental impact and their compatibility with sustainable environmental systems. The research is concerned with analyzing the types of interactive facades by identifying: the interactive idea, interaction technology, and the environmental impact. Interactive facades vary with types of dynamic interaction: (mechanical, delusion, by user, media) which affect the interface's shape, its interaction and its environmental impact. The interactive façade technology depends on the applied cladding technology, including “ventilated facades,” which depend on the existence of the installation structure, and is characterized by reducing the amount of building materials, reducing the temperature of the building and rationalizing electrical energy consumption. The interactive and smart façades include advanced external cladding materials of a reactive nature, such as Alucopond cladding, Interactive paints and Smart glasses.... Interactive cladding materials have industrial and environmental specifications, which are: resistance to weather, sunlight, humidity, pests and fires, reducing electrical energy consumption, and making use of Natural solar energy, longevity and ease of maintenance. Interactive and smart interfaces are compatible with sustainable environmental systems when they contain environmental impact criteria.
Keywords: الأنظمة البيئية -- تكنولوجيا البناء -- الواجهات المعمارية -- منتجات التكسية